The evolution of belief systems: a journey through human thought and spiritual discovery - Norman, Nurul Ain (The Institute of Oriental Philosophy, 2025)
This article traces the evolution of belief systems from early animistic practices to organized religions and modern philosophical frameworks. By analyzing their comparative and thematic patterns, this study highlights how belief systems adapt to cultural, social, and intellectual shifts, with each era marking a distinct stage in humanity 's pursuit of understanding. It emphasizes that religion is both a cultural and historical phenomenon which mirrors individual experiences shaped by Divine guidance. This article puts forth thinking, embracing, and believing, i.e. an empirical framework of belief—symbolizing its metamorphosis through intellectual reflection, unfeigned connection, and deep conviction. These stages illustrate how humanity's growing awareness of the Divine acclimatizes to the needs and perspectives peculiar to each historical period. The findings, stemming from a historical and comparative approach, reveal that belief systems unceasingly shape human thought, morality, and identity, serving as both foundations for individual spiritual growth and milestones in humanity's shared quest for understanding, truth, and connection to a higher purpose.